DEVELOPMENT OF A CHATBOT TO MOTIVATE REGULAR BLOOD DONATION - Serrano, Paulo Henrique; Becker, Valdecir (Revista Interface Tecnológica, 2025)
This research presents the development of the chatbot Socorro, which encourages voluntary and regular blood donation through the instant messaging platform Telegram. The research adopted the Design Science Research methodology for the creation and evaluation of the artifact. Socorro was conceived to improve awareness of the importance of blood donation by offering features such as access to donation history, reminders for new donations, and the formation of donation groups. The application of specific usability heuristics for chatbots highlighted the clarity of language, preservation of context, and usability of the chatbot and allowed for the identification and improvement of interaction messages, emphasizing the potential of such technologies to promote public health and well-being practices. The results indicate that virtual assistants can be used to increase interaction in desirable social practices and, in this case, potentially integrate into blood center systems, offering an effective solution to enhance awareness and social participation in blood donation.
Keywords: Chatbot; Health Communication; Blood Donation; User-centered Design